Estudo, por modelagem molecular, da inibição da enzima acetohidroxiácido sintase utilizando diferentes derivados pirimidinilsalicilatos - Silva, Viviane Aparecida (2017)
Herbicides inhibitors of the enzyme acetohydroxyacid synthase (AHAS) present high efficiency in the inhibitory activity with low doses of application and low toxicity for man and the environment. However, several weeds are getting resistence to some classes of herbicides, mainly in the case of AHAS group. Therefore, a proper computational planning of new bioactive compounds is crucial area to model new herbicides. In this study, the enzyme-herbicide interactions were analyzed from the analogous derivated of the pyrimidinylsalicylates group (PSA) which are AHAS inhibitors using quantum- mechanical and molecular docking calculations. The molecular properties obtained after running computer calculation shown that the volume and molecular area can make influence on the inhibition capacity of the ligand, neverthenless, the substituent group has more influence on this parameter. Electronical properties from the HOMO orbitals can certanly make influence on the biological activity due its electron donor capability. The binding free energies of the ligand on the enzyme after docking calculation ranged from - 1.88 to 4.50 kcal mol- 1 , whereas, H, CH3, COCH3 , OH, NO2 and NH2 had the best scored binding energies as substituent groups. Those favorable binding free energies can be justified by the intermolecular interactions between PSAs ligands and AHAS active site residues. In terms of effiency, hydrogen bonds formation can be explained by carboxylate group from the ligands and ARG-377 group from AHAS.